Buprenorphine use in cachectic cancer patient – case report - Dzierżanowski, Tomasz (Medycyna Paliatywna/Palliative Medicine, 2010)
In this case of extremely cachectic female patient with small cell lung cancer and alcohol addiction, buprenorphine appeared an effective, well tolerated and safe analgesic, in spite of very low body weight and mere fat tissue of the patient